Pengaruh Aplikasi Tiktok terhadap Karakter Sopan Santun Siswa Kelas V SD Negeri Panciro Kec. Bajeng Kab. Gowa - Kaharuddin Kaharuddin; Ashar Ashar; Ummu Kalsum (Journal on Education, 2024)
This research aims to examine the influence of the TikTok application on the polite character of fifth grade students at Panciro State Elementary School, Barombong District, Gowa Regency. Based on the problems studied, the method and type of this research uses Ex-Post Facto research or measurement after the event and correlational descriptive using a quantitative approach, which focuses on analyzing numerical data processed using statistical methods. This method was used because this research sought to find out whether there was an influence between the TikTok application on the polite character of fifth grade students at Panciro State Elementary School. The results of the analysis of data interpretation concluded that there was an influence of the Tiktok application on students' polite character. This can be seen from the results of the hypothesis test where the overall calculated r is 0.808459, r table 0.312 with a significance of 0.05 and if you look at the correlation coefficient interpretation table, the level of influence is on a strong scale. Therefore, Ha accepts that there is an influence of the Tiktok application on students' polite character.